Cultural adaptation. (1st March 2015) - Ley, Graham
Culture can be readily seen as a repository for adaptation, but if attention is given more resolutely to the idea of the plurality of cultures, then it is possible that we should adjust that rather simplistic perception drastically. This article presents a theory, expressed in broad but comprehensive terms, of the place of adaptation in the constitution of theatre, at many different originative moments. It also goes beyond the realms of film and theatre to suggest that human cultures not only express adaptation, but are founded from the beginning on the capacities of a uniquely adaptive species, from constant adjustments in material existence through to artistic practice. The article also examines how the idea of cultural adaptation can be found to be operative within current terminology applied to performance and society. Adaptation is the natural state of human cultures, not merely a facility within them, and the author draws on wide reading in the social sciences and the history of theatre to support his thesis.